Las ψυχας ενέρων del fr. 912 Kannicht de Eurípides y la columna VI del Papiro de Derveni - Macías Otero, Sara Mª (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2007)
The Euripides’ 912 Kannicht fragment is very dark in its religious interpretation. It is a prayer whose ninth verse demands the presence of «the souls of the dead» so they help to know the truth about a number of existential questions. This ninth verse is one of the most conflictive points in this passage, specially in determining these souls’ identity. I propose to think them a kind of intermediate beings who would help the faithful in a moment of the ritual, and who would be identified with benefactor daimones, because they are also a kind of souls. The Eumenides would also be this type of daimones, while the Erinis would be avenging daimones that, on the contrary, would hinder the initiatic process. In the Derveni Papyrus, the Eumenides are mentioned as souls who have been pacified, and who are intermediaries between men and gods, and vice versa. The testimonies that I have collected of Plato, Plutarch and Porphyry speak of daimones as a kind of souls that mediate between the human and the divine worlds, and that, when they are beneficial, give revelations and guide humans. In Euripides’ 912 fragment a religious picture is presented that is coherent with the orphic beliefs and complementary of the Derveni Papyrus in relation to the daimones’ presence in orphic ritual.